2022
DOI: 10.3390/ijms23042077
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenicity within the LPS Structure in Relation to the Chosen Genomic and Physiological Features of the Plant Pathogen Pectobacterium parmentieri

Abstract: Pectobacterium parmentieri is a pectinolytic plant pathogenic bacterium causing high economic losses of cultivated plants. The highly devastating potential of this phytopathogen results from the efficient production of plant cell wall-degrading enzymes, i.e., pectinases, cellulases and proteases, in addition to the impact of accessory virulence factors such as motility, siderophores, biofilm and lipopolysaccharide (LPS). LPS belongs to pathogen-associated molecular patterns (PAMPs) and plays an important role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…These adhesion abilities, combined with the production of plant cell wall-degrading enzymes, T3SS, mobility and biofilm formation are important virulence factors of the pathogenic bacteria in plants (Mole et al, 2007). It was confirmed that OPSs of some Pectobacterium and Dickeya strains had an impact on the development of bacterial plant diseases (Bartnik et al, 2021(Bartnik et al, , 2022Duprey et al, 2019;Evans et al, 2010;Ossowska et al, 2022;Żołędowska et al, 2018; Figure 1). The OPSs also contribute to the resistance of phytopathogens to antimicrobial compounds (barrier function), which presumably promotes the ability to infect plants.…”
Section: P Otential O -P Olysaccharide Fun C Ti On S Rel Ated To Pl A...mentioning
confidence: 80%
See 4 more Smart Citations
“…These adhesion abilities, combined with the production of plant cell wall-degrading enzymes, T3SS, mobility and biofilm formation are important virulence factors of the pathogenic bacteria in plants (Mole et al, 2007). It was confirmed that OPSs of some Pectobacterium and Dickeya strains had an impact on the development of bacterial plant diseases (Bartnik et al, 2021(Bartnik et al, , 2022Duprey et al, 2019;Evans et al, 2010;Ossowska et al, 2022;Żołędowska et al, 2018; Figure 1). The OPSs also contribute to the resistance of phytopathogens to antimicrobial compounds (barrier function), which presumably promotes the ability to infect plants.…”
Section: P Otential O -P Olysaccharide Fun C Ti On S Rel Ated To Pl A...mentioning
confidence: 80%
“…Recent structural studies of OPSs isolated from two other strains, namely P. parmentieri SCC3193 and IFB5432, indicate that these OPSs also have identical structures. Moreover, the mentioned OPSs have only a main chain, consisting of two residues of d-Gal, in pyranose and furanose form, two residues of d-Glc and a very rare residue of 5,7 -diamino-3,5,7,9-tetradeoxyl-glycerol-manno-non-2-ulosonic acid (Ossowska et al, 2022; Table 1). The latter component was reported previously in the repeating unit of the OPS isolated from Shigella boydii type 7.…”
Section: Comp Os Ition and S Truc Tur Al D Iver S It Y Of O -P Olysac...mentioning
confidence: 99%
See 3 more Smart Citations